The Helix and Slant Helices Generated by non-Degenerate Curves in M3(?0)?E24 - Almaz, Fatma; Kulahci, Mihriban Alyamac (My University, 2021)
In this paper, we investigate helix and slant helices using non-degenerate curves in term of Sabban frame in de Sitter 3-space or Anti de Sitter 3-space M3(?0). Furthermore, in M3(?0) 3-space the necessary and sufficient conditions for the non- degenerate curves to be slant helix are given.
Keywords: Helix; slant helix; Sabban frame; M3 (?0)?E2 4 3-space